Leaf spot disease of coconut seedling and its eco-friendly management - Khan, MAH; Hossain, I (Journal of the Bangladesh Agricultural University, 2014)
The effect of weather on prevalence of seedling diseases of coconut during 2010-11 and 2011-12 in different areas of Bangladesh was studied to develop an environment friendly disease management practice. Pestalotia palmarum was isolated and identified from leaf having spot. Incidence and severity of grey leaf spot at seedling stage were determined and significant variations were observed depending on weather factors as well as locations. Occurrence of seedling disease was significantly influenced by temperature, rainfall and relative humidity. Comparative effectiveness of BAU-Biofungicide either alone or in combination with two fungicides viz. Bavistin or Dithane M-45 was evaluated on coconut seedling in the nursery. Among the treatments applied, Trichoderma harzianum based BAU-Biofungicide either alone or in combination with Bavistin (0.2%) as an excellent biocontrol means in controlling leaf spot disease of coconut. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19894 J. Bangladesh Agril. Univ. 11(2): 199-208, 2013